(untitled) (Jurnal Bahasa, 2014)
This article aims to analyse the debuccalisation process in English loanwords in Kelantanese dialect. Debuccalisation is a process of sound change whereby a consonant loses its original place of articulation (place feature) and becomes [h] or [ ]. From the secondary data obtained from the previous study by Shapri (1980) and constraint-based analysis, English loanwords in the Kelantanese dialect that undergo the phonological process of debuccalisation will be discussed in this present study. The results show that this process not only involves the consonants /p/, /t/ and /k/ in the Kelantanese dialect, as in /kica/ "kicap", /jahe/ "jahit’ and /las/ "lasak’, but also other consonants such as /f/, /t/, /b/ dan /g/, as in /pla/ "plug’. The observations from the data are that the phonological process of debuccalisation in English loanwords in the Kelantanese dialect only occurs in the coda of a final syllable. Keywords: English, optimality theory, debuccalisation, loanwords, Kelantanese dialect